Durability of Stretta Radiofrequency Treatment for GERD: Results of an 8-Year Follow-Up - Luca Dughera; Gianluca Rotondano; Maria De Cento; Paola Cassolino; Fabio Cisarò (Gastroenterology Research and Practice)
From June 2002 to March 2013 26 patients that underwent Stretta procedure (16 females, 10 males) reached to date an eight-year follow-up. Primary end point of the study was to verify the durability of the procedure at this time. All patients underwent clinical evaluation by upper endoscopy, oesophageal pressure, and pH studies. For each patient 8-year data were compared to those recorded at baseline and at 4 years. There was a significant decrease in both heartburn and GERD HRQL scores at 4 years (P=0.001) and at 8 years (P=0.003) as well as a significant increase of QoL scores at each control time (mental SF-36 and physical SF-36, P=0.001). After 4 and 8 years, 21 patients (80.7%, P=0.0001) and 20 patients (76.9%, P=0.0001) were completely off PPIs. Median LES pressure did not show significant amelioration at 4 and 8 years and mean oesophageal acid exposure significantly improved at 4 years (P=0.001) but returned to baseline values after 8 years. This further follow-up study of ours from four to eight years confirms that RF energy delivery for GERD provides durable improvement in symptoms and in quality of life and reduces antireflux drugs consumption.